2022
DOI: 10.5334/gh.1103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Acceptability of a Mobile Phone Text Messaging Intervention to Improve Blood Pressure Control (TEXT4BP) among Patients with Hypertension in Nepal: A Feasibility Randomised Controlled Trial

Abstract: Background: Uncontrolled blood pressure (BP) is the leading cause of preventable deaths in low-and middle-income countries. mHealth interventions, such as mobile phone text messaging, are a promising tool to improve BP control, but research on feasibility and effectiveness in resource-limited settings remains limited.Objective: This feasibility study assessed the effectiveness and acceptability of a mobile phone text messaging intervention (TEXT4BP) to improve BP control and treatment adherence among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 49 publications
4
44
0
1
Order By: Relevance
“…As these were the result of a thematic analysis, there are cases of multiple observations of the same theme in the same article; therefore, the frequency may not have aligned with the number of references. Of the 92, there were 31 (34%) instances of an increase in physical health [ 30 , 33 , 39 - 42 , 44 , 47 , 49 , 51 - 55 , 57 , 58 ]. This theme included maximum oxygen consumption, comparison of bad cholesterol with good cholesterol, pain, diastolic blood pressure, systolic blood pressure, hypoglycemia, lipids, overall blood pressure, average blood sugar over last 3 months, physical function, fasting blood glucose, cholesterol, and BMI.…”
Section: Resultsmentioning
confidence: 99%
“…As these were the result of a thematic analysis, there are cases of multiple observations of the same theme in the same article; therefore, the frequency may not have aligned with the number of references. Of the 92, there were 31 (34%) instances of an increase in physical health [ 30 , 33 , 39 - 42 , 44 , 47 , 49 , 51 - 55 , 57 , 58 ]. This theme included maximum oxygen consumption, comparison of bad cholesterol with good cholesterol, pain, diastolic blood pressure, systolic blood pressure, hypoglycemia, lipids, overall blood pressure, average blood sugar over last 3 months, physical function, fasting blood glucose, cholesterol, and BMI.…”
Section: Resultsmentioning
confidence: 99%
“…Bhandari et al also reported decreased systolic and diastolic blood pressure in the intervention group that was exposed to automated text messages and video messages. In addition, the intervention arm showed an improvement in compliance with antihypertensive therapy (p<0.001), medication adherence (p<0.001), medication adherence self-efficacy (p=0.023), and knowledge of hypertension and its treatment (p=0.013) [26]. [23].…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have discussed a couple of outcomes, more appearing to be a reduction in blood pressure, systolic and diastolic blood pressure, user acceptance and user compliance, medication adherence, and reduced hypertensive symptoms. Of the 13 studies, 10 [ 19 , 20 , 22 - 26 , 29 - 31 ] have reported a significant reduction in blood pressure following the use of automated messages, video messages, self-monitoring applications, and mobile applications. Davidson et al reported using reminders and signals as mobile health interventions among individuals with essential hypertension [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations